STRATEGI PEMERINTAH KABUPATEN SIAK DALAM MENINGKATKAN INDEKS PEMBANGUNAN MANUSIA TAHUN 2011-2016 - Septiatuti, Endang; Yusri, Ali (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Granting of regional autonomy to accelerate the realization of community welfare through improving services, empowerment and community participation. The spirit of reform in the field of politics, government and development and society has colored the journey of regional autonomy for the achievement of duties and functions of governance and development, including human development. Human development is always at the forefront of development planning, since the essence of development is human development, the improvement of this priority will also improve the welfare of society as measured by the Human Development Index. Siak Regency is one of the Daerah Otonomi Baru (DOB) in Indonesia which is ranked fifth best of 34 Districts/Cities in Indonesia, and has been named Indonesia’s Best New Autonomous Region, from 10 New Autonomous Region as New Autonomous Region. Then from the 10 new autonomous regions that get the highest score is Siak Regency given by Indonesian Governance Index (IGI). The purpose of this research is to know the strategy undertaken Siak Regency Government in improving Human Development Index year 2011-2016. Tis research is a qualitative approach, with descriptive type of data collection is done by observation, interview and documentation. This research was conducted in Siak Regency. The result of this research is the success of human development which is marked by the increase of Human Development Index is a concrete manifestation that Siak regency has perfomed its duty in giving maksimal service to society in building quality of human life to achieve decent living. Siak Regency Government has made policy through program that refers to the improvement of Human Development Index, among others: (1) improvement of health degree through life expectancy, (2) increasing the scope and quality of education service, (3) improving decent living standards of the community through the community economy. So with the increasing Human Development Index, the Government has been able to improve the welfare of the community. Keywords: Strategy, Human Development Index